Synthesis and Biological Evaluation of Cremastrine and an Unnatural Analogue - Hahn, Kristopher N. (2012)
In this Letter, we describe the first total synthesis of cremastrine, a pyrrolizidine alkaloid from Cremastra appendiculata, with anticholinergic activity as well as an unnatural analogue. The streamlined synthesis proceeds in 9 steps, 7 steps longest linear sequence, in 25.2% overall yield, and features novel methodology to construct the pyrrolizidine core. Biological evaluation of cremastrine and the unnatural analogue indicated that both are pan-mAChR functional antagonists.